Humor in Love Poems by Hafez - ahmad hashemi (Matn/Pizhūhī-i Adabī, 2012)
The present study introduces some artistic delicacies and techniques used by Hafez in creation of love humor. With a different view towards humor, this paper considers Hafez poems as one of the most serious, effective, and artistic works and attempts to discuss smart techniques used by Hafez. It also analyzes the factors influencing the humor in his work. It is concluded that humor is one of the most significant concerns in language and mind of Hafez in creation of love atmospheres and are used in a very mystic and complicated way.